Performance and emissions of an electronic control common-rail diesel engine fuelled with liquefied natural gas-diesel dual-fuel under an optimization control scheme. (May 2019) - Song, Jiantong; Zhang, Chunhua; Lin, Guoqing; Zhang, Quanchang
In order to reduce the fuel consumption and hydrocarbon and CO emissions of liquefied natural gas-diesel dual-fuel engines under light loads, an optimization control scheme, in which the dual-fuel engine runs in original diesel mode under light loads, is used in this paper. The performance and exhaust emissions of the dual-fuel engine and the original diesel engine are compared and analyzed by bench tests of an electronic control common-rail diesel engine. Experimental results show that the brake-specific fuel consumption and hydrocarbon and CO emissions of the liquefied natural gas-diesel dual-fuel engine are not deteriorated under light loads. Compared with diesel, the brake power and torque of dual-fuel remain unchanged, the brake-specific fuel consumption decreases, and the smoke density and CO2 emissions of dual-fuel decrease, while the hydrocarbon and CO emissions increase, and there is no significant difference in NOx emissions.